Hemodynamic and Functional Correlates of Concentric vs. Eccentric LVH in a Community-Based Sample With Prevalent Volume-Dependent Hypertension. (11th August 2021) - Bello, Hamza; Norton, Gavin R; Peterson, Vernice R; Libhaber, Carlos D; Mmopi, Keneilwe N; Mthembu, Nonhlanhla; Masiu, Mohlabani; Da Silva Fernandes, Daniel; Bamaiyi, Adamu J; Peters, Ferande; Sareli, Pinhas; Woodiwiss, Angela J
Abstract: BACKGROUND: Whether in volume-dependent primary hypertension, concentric left ventricular (LV) remodeling beyond hypertrophy (LVH) represents the impact of a pressure rather than a volume overload, is unclear. METHODS: Using central arterial pressure, and aortic velocity and diameter measurements in the outflow tract (echocardiography), we determined the factors that associate with concentric LVH or remodeling in a community of African ancestry ( n = 709) with prevalent volume-dependent primary hypertension. RESULTS: Both left ventricular mass index (LVMI) and relative wall thickness (RWT) were positively and independently associated with end diastolic volume (EDV), stroke volume (SV), and peak aortic flow (Q) ( P < 0.05 to <0.0001). However, neither LVMI nor RWT were positively and independently associated with systemic vascular resistance (SVR), or aortic characteristic impedance (Zc) or inversely associated with total arterial compliance (TAC). Consequently, both concentric ( P < 0.0001) and eccentric ( P < 0.0001) LVH were associated with similar increases in EDV, SV, and either office brachial, central arterial, or 24-hour blood pressures (BP), but neither increases in SVR or Zc nor decreases in TAC. LV RWT, but not LVMI was nevertheless independently and inversely associated with myocardial systolic function (midwall shortening and s′) ( P < 0.05 to <0.005) and decreases in LV systolic function were noted in concentric ( P < 0.05), but not eccentric LVH. CONCLUSIONS: In volume-dependent primary hypertension, concentric LVH is determined as much by volume-dependent increases in systemic flow and an enhanced BP as eccentric LVH. Concentric remodeling nevertheless reflects decreases in systolic function beyond LVH. Graphical Abstract: